Recording of Circuit Television (CCTV) as Evidence in The Process of Evidence on Criminal Case in Indonesia - H. Khanafi Khanafi; Sri Endah Wahyuningsih (Jurnal Daulat Hukum, 2018)
Proof is the most decisive stage of the proceedings, considering at this stage will be determined whether or not proved the defendant committed a criminal act as indicted prosecutors. The issues in this thesis is whether the CCTV recording can be used as evidence in the process of proving a criminal case in Indonesia and what obstacles and solutions if CCTV be used as evidence in the process of proving a criminal case. The approach used problem is empirical juridical approach. The data used are primary data, secondary data and data tertiary. While the method of data collection was done by using literature study and field work and data analysis in this research is a descriptive qualitative. The results of research and discussion addressing that (1) a video of CCTV can be used as a valid legal evidence that they meet the requirements stipulated in the ITE Law Article 5 of Act No. 19 of 2016. (2) barriers CCTV as evidence in criminal cases is the lack of lighting and lack of ITE experts from the big city, so the result is dark and the image quality is less clear, but the CCTV still can be used as electronic evidence for CCTV still in the original form. CCTV evidence greatly assist the police to carry out investigations in criminal cases of theft and murder. Suggestions in this study were: Investigator should report the crime to the local Court-related issues CCTV recording to be used as evidence.Keywords: Closed Circuit Television (CCTV); Evidence; Criminal Law.